Starch-based hard carbon negative electrode material, preparation method thereof and lithium ion battery
By reacting polyvinyl alcohol as a self-sacrificial template with starch and lithium hydroxide, a starch-based hard carbon negative electrode material was prepared, which solved the complex preparation process in the prior art, and achieved the effect of simplifying the process and improving the electrochemical performance.
Patent Information
- Application Number
- CN202510222596.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-02-27
AI Technical Summary
In the prior art, the preparation process of porous hard carbon anode materials is complicated, the process is complicated and the energy consumption is high.
Polyvinyl alcohol is used as a self-sacrificial template to form a spherical precursor through reaction with starch and lithium hydroxide, and calcined under an inert gas atmosphere to obtain a starch-based hard carbon negative electrode material, simplifying the preparation process.
The subsequent steps of removing templates are reduced, the process and energy consumption are reduced, and the hard carbon negative electrode material with porous structures is helped to generate and improve electrochemical performance.
Smart Images

Figure MTIZTWYVY4ML9J9YSIZSU1FOIXCW3FFPL4LINYVA
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to a starch-based hard carbon anode material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] The anode material is one of the important factors determining the comprehensive performance of lithium-ion batteries. At present, the anode materials of lithium-ion batteries mainly focus on graphite, hard carbon, soft carbon, etc. Among them, hard carbon has a dispersed crystal structure, stable structure, easy lithium-ion deintercalation and intercalation, which is convenient for increasing the output power of the battery, and has a long charge-discharge cycle life and good safety performance. Therefore, it has become the focus of research on anode materials.
[0003] The raw materials for traditional preparation of hard carbon anode materials mainly include non-renewable mineral resources such as coal, resin, and asphalt. In recent years, due to the shortage of mineral resources, the development and application of traditional hard carbon anode materials have been restricted. Under this premise, biomass resources have become the focus of research and attention because they contain rich carbon elements and have the advantages of being renewable, low-pollution, and widely distributed. Using biomass resources to prepare hard carbon anode materials.
[0004] Starch is a raw material belonging to biomass resources, which has the advantages of low price, wide source, and rich carbon elements, and has great potential in the preparation of carbon materials. For electrode materials, the introduction of a porous structure usually has a great impact on electrochemical performance. At present, in the preparation process of hard carbon anode materials, a porous structure is usually prepared by a fixed template method. This preparation method requires the removal of the fixed template later. In terms of process, there is an additional cleaning process, the process is complicated, and the energy consumption is high.
[0005] In view of this, providing a preparation method for a starch-based hard carbon anode material with a simple process is a technical problem that needs to be solved urgently at present. Summary of the Invention
[0006] In order to solve the problem of the complex preparation process of porous hard carbon anode materials in the prior art, the present invention provides a preparation method for a starch-based hard carbon anode material. This preparation method uses polyvinyl alcohol as a self-sacrificing template to synthesize a starch-based hard carbon anode material with a porous structure, and there is no need to remove the template later, which simplifies the preparation process and solves the problem of the complex preparation process of porous hard carbon anode materials in the prior art.
[0007] The technical solution adopted by the present invention to solve its technical problems is: A preparation method for a starch-based hard carbon anode material, comprising the following steps: S1: Mix a polyvinyl alcohol solution and a lithium hydroxide solution, add starch, stir, and then add a haloacid for reaction to obtain a reaction mixture; S2: Dropwise inject the reaction mixture into a liquid nitrogen bath to obtain spherical precursors. S3: Calcinate the spherical precursors under an inert gas atmosphere to obtain a starch-based hard carbon anode material.
[0008] Optionally, the mass ratio of the starch to polyvinyl alcohol is (8 - 10):1.
[0009] Optionally, the mass ratio of lithium hydroxide to polyvinyl alcohol is 1:5.
[0010] Optionally, the starch is selected from at least one of cereal starch, potato starch, and legume starch.
[0011] Optionally, step S3 includes: Under an inert gas atmosphere, heat the spherical precursors from room temperature to 200°C, then from 200°C to 400°C, and then from 400°C to 900 - 1000°C for calcination to obtain a starch-based hard carbon anode material.
[0012] Optionally, when heating the spherical precursors from room temperature to 200°C, the heating rate is 5°C / min.
[0013] Optionally, when heating the spherical precursors from 200°C to 400°C, the heating rate is 1°C / min.
[0014] Optionally, when heating the spherical precursors from 400°C to 900 - 1000°C, the heating rate is 5°C / min.
[0015] Another object of the present invention is to provide a starch-based hard carbon anode material prepared by the preparation method of the starch-based hard carbon anode material as described above.
[0016] Another object of the present invention is to provide a lithium-ion battery including the starch-based hard carbon anode material as described above.
[0017] The beneficial effects of the present invention are as follows: The preparation method of the starch-based hard carbon anode material provided by the present invention uses polyvinyl alcohol as a self-sacrificial template, which not only acts as a template during the preparation process but also can be carbonized into active substances at high temperatures. This not only reduces the subsequent steps of removing the template, simplifies the process and reduces energy consumption, but also helps the formation of a porous structure in the hard carbon anode material and is conducive to the regulation of the pore structure. At the same time, combined with the in-situ generated lithium halide inside the starch as a lithium supplement salt, while simplifying the preparation steps, a porous carbon anode material with excellent electrochemical performance is prepared. Detailed Embodiments
[0018] The present invention will now be described in further detail. The embodiments described below are exemplary and are intended to explain the present invention, and should not be construed as limiting the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0019] To solve the problem of the complex preparation process of porous hard carbon anode materials in the prior art, the present invention provides a method for preparing a starch-based hard carbon anode material, and the preparation method includes the following steps: S1: Mix a polyvinyl alcohol solution and a lithium hydroxide solution, add starch, and stir. Preferably, after stirring at 40 - 50 °C for 3 - 6 h, add a haloacid for reaction to obtain a reaction mixture; Among them, the polyvinyl alcohol solution is preferably prepared according to the following method: According to the formulation amount, add polyvinyl alcohol (PVA) powder to deionized water, stir at room temperature for 10 - 50 minutes to prevent caking, and then stir at 80 - 100 °C for 20 - 50 minutes to obtain a transparent solution. Cool to room temperature to obtain a polyvinyl alcohol solution; In this step, after fully mixing the polyvinyl alcohol solution and the lithium hydroxide solution, adding starch helps to infiltrate lithium hydroxide into the starch; then adding a haloacid to react lithium hydroxide with the haloacid to generate lithium halide; since lithium hydroxide has infiltrated into the starch, lithium halide can be in-situ generated within the starch; lithium halide is used as a prelithiation salt here, which is beneficial to improving the first efficiency of porous carbon; the present invention preferably has the same molar amount of haloacid and lithium hydroxide; S2: Dropwise inject the reaction mixture into a liquid nitrogen bath and quickly freeze it to obtain spherical precursors; In this step, the liquid nitrogen bath spheroidizes the precursors, which is beneficial to the shaping of the subsequent carbonized materials of the precursors; S3: Calcinate the spherical precursors in an inert gas atmosphere. Preferably, wash the carbonized sample with deionized water to remove any potential impurities, and then dry it at 85 °C for 12 hours. Part of the lithium halide remains in the pore structure of the porous carbon to obtain a starch-based hard carbon anode material.
[0020] Based on the fact that both polyvinyl alcohol and starch contain a large number of hydroxyl groups, when starch is mixed with a polyvinyl alcohol solution, a physical cross-linked network can be formed through hydrogen bonds. This interaction can enhance the uniformity of the mixed system and provide a stable precursor structure for subsequent carbonization. At the same time, by first mixing lithium hydroxide with polyvinyl alcohol and then adding starch, lithium hydroxide can be encapsulated in the physical cross-linked network formed by polyvinyl alcohol and starch. Then, a lithium halide pre-lithium salt is introduced by adding a halogenated acid to react with lithium hydroxide, so that the generated lithium halide is located in the cross-linked network, thereby ensuring the electrochemical performance of the anode material. Compared with the method of directly adding lithium halide, the lithium halide located in the cross-linked network is more stable in position and can achieve the pre-lithiation effect for a long time.
[0021] During the subsequent calcination process, the hydroxyl groups of polyvinyl alcohol and starch can undergo a condensation reaction at high temperature, which helps to further enhance the cross-linking degree of the carbon skeleton and form a three-dimensional network structure. This cross-linking effect can inhibit the generation of disordered structures during carbonization and improve the mechanical strength and conductivity of hard carbon. During the carbonization process, the decomposition of starch will produce gases such as CO 2 、H 2 O, etc., thereby generating pores in the material. The presence of polyvinyl alcohol helps to form a uniform carbon matrix, and the synergistic effect of the two regulates the specific surface area and pore size distribution of hard carbon. At the same time, the carbonization of polyvinyl alcohol tends to form a short-range ordered graphite microcrystalline structure, which helps to improve conductivity, while the carbonization product of starch is usually amorphous carbon. The mixing of the two can optimize the lithium storage performance of hard carbon by adjusting the microcrystalline size and defect density.
[0022] The preparation method of the starch-based hard carbon anode material provided by the present invention uses polyvinyl alcohol as a self-sacrificial template, which not only acts as a template during the preparation process but also can be carbonized into active substances at high temperature. This not only reduces the subsequent steps of removing the template, reduces the process and energy consumption, but also helps the generation of porous structures in the hard carbon anode material and helps to realize the regulation of pore structures. At the same time, combined with the in-situ generated lithium halide in starch as a pre-lithium salt, while simplifying the preparation steps, a porous carbon anode material with excellent electrochemical performance is prepared.
[0023] When the content of polyvinyl alcohol in the system is too high, the porosity of the carbon material will be inhibited; when the content of polyvinyl alcohol is too low, the mechanical properties and electrical conductivity of the carbon material will deteriorate. To balance the porosity, mechanical properties and electrical conductivity of the starch-based hard carbon anode material, the present invention preferably selects the mass ratio of starch to polyvinyl alcohol to be (8-10):1.
[0024] In the present invention, the polyvinyl alcohol solution is an aqueous solution of polyvinyl alcohol, and the lithium hydroxide solution is an aqueous solution of lithium hydroxide; preferably, the mass concentration of the polyvinyl alcohol solution in step S1 is 10%, the mass concentration of the lithium hydroxide solution is 10%, and further preferably, the mass ratio of lithium hydroxide to polyvinyl alcohol is 1:5.
[0025] Preferably, the starch in the present invention is selected from at least one of cereal starch, potato starch, and legume starch.
[0026] To ensure the mechanical properties and electrochemical properties of the starch-based hard carbon anode material, preferably, step S3 in the present invention includes: under an inert gas atmosphere, heating the spherical precursor from room temperature to 200 °C, then from 200 °C to 400 °C, and then from 400 °C to 900 - 1000 °C for calcination to obtain the starch-based hard carbon anode material.
[0027] During this calcination process, at 200 - 400 °C, the starch first undergoes dehydration and chain scission to generate small molecule organic substances such as glucose, and then further decomposes into tar and carbon black, which is the tar removal stage of the starch; at the same time, polyvinyl alcohol undergoes a dehydration reaction to generate a conjugated double bond structure, while releasing small molecules such as water and acetic acid. The condensation reaction of its molecular chains can form a stable aromatic ring structure, promoting the formation of graphite microcrystals; and, the cross-linking and condensation reaction of the hydroxyl groups of starch and polyvinyl alcohol form a three-dimensional carbon skeleton; further, calcination and carbonization at 900 - 1000 °C form a starch-based hard carbon anode material with a porous structure.
[0028] Preferably, in step S3 of the present invention, when heating the spherical precursor from room temperature to 200 °C, the heating rate is 5 °C / min; preferably, when heating the spherical precursor from 200 °C to 400 °C, the heating rate is 1 °C / min to avoid the collapse of the pore structure; preferably, when heating the spherical precursor from 400 °C to 900 - 1000 °C, the heating rate is 5 °C / min.
[0029] Another object of the present invention is to provide a starch-based hard carbon anode material, which is prepared by the preparation method of the starch-based hard carbon anode material as described above.
[0030] In the preparation process of the starch-based hard carbon anode material provided by the present invention, polyvinyl alcohol is used as a self-sacrificial template. Polyvinyl alcohol not only acts as a template but also can be carbonized into active substances at high temperatures. This not only reduces the subsequent steps of removing the template, reduces the processes and energy consumption, but also helps the formation of a porous structure in the hard carbon anode material and helps to realize the regulation of the pore structure; at the same time, combined with the in-situ generated lithium halide in the starch as a lithium supplement salt, while simplifying the preparation steps, a porous carbon anode material with excellent electrochemical properties is prepared.
[0031] Another object of the present invention is to provide a lithium-ion battery, which includes the starch-based hard carbon negative electrode material as described above.
[0032] For the lithium-ion battery provided by the present invention, the adopted starch-based hard carbon negative electrode material uses polyvinyl alcohol as a self-sacrificing template during the preparation process. Polyvinyl alcohol not only acts as a template but also can be carbonized into active substances at high temperatures. This not only reduces the subsequent steps of removing the template, simplifies the process and reduces energy consumption, but also helps to generate a porous structure in the hard carbon negative electrode material and facilitates the regulation of the pore structure. At the same time, combined with the in-situ generated lithium halide inside the starch as a lithium supplement salt, while simplifying the preparation steps, a porous carbon negative electrode material with excellent electrochemical performance is prepared, which helps to improve the electrochemical performance of the lithium-ion battery.
[0033] To make the above objects, features and advantages of the present invention more obvious and understandable, the following detailed description of the specific embodiments of the present invention is provided.
[0034] Example 1 This example provides a preparation method of a starch-based hard carbon negative electrode material, and the preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder to deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration transparent polyvinyl alcohol solution, and cool it to room temperature; then carefully mix 500 g of the polyvinyl alcohol solution with 100 g of a 10% mass concentration LiOH solution, add 450 g of corn starch, stir at 45 °C for 5 h, and then add dilute hydrochloric acid with the same amount of substance as lithium hydroxide to react lithium hydroxide with hydrochloric acid to generate lithium chloride, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain spherical precursors; S3: Use a tube furnace under an argon atmosphere to heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of corn starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, and it is heated from 400 °C to 900 °C, and kept at 900 °C for 3 h to complete the carbonization process. The reacted solid mixture is ultrasonically cleaned in deionized water for 4 hours to wash off the excess lithium chloride, and then dried at 85 °C for 12 hours. The remaining lithium chloride remains in the pore structure of the porous carbon to participate in the prelithiation effect during the subsequent charge and discharge process, obtaining the target product, the starch-based hard carbon negative electrode material.
[0035] The specific surface area of this negative electrode material was tested using a specific surface area tester, and the specific surface area was 164 m 2 / g.
[0036] Example 2 This example provides a preparation method of a starch-based hard carbon anode material, and the preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder into deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration polyvinyl alcohol transparent solution, and cool it to room temperature; then carefully mix 500 g of the polyvinyl alcohol solution with 100 g of a 10% mass concentration LiOH solution, add 450 g of wheat starch, stir at 45 °C for 5 h, and then add dilute hydrochloric acid with the same amount of substance as lithium hydroxide to react lithium hydroxide with hydrochloric acid to generate lithium chloride, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain small spherical precursors; S3: Use a tube furnace under an argon atmosphere to heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar discharge stage of wheat starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, and it is heated from 400 °C to 950 °C, and kept at 950 °C for 2.5 h to complete the carbonization process. Ultrasonically clean the reacted solid mixture in deionized water for 4 hours to wash off the excess lithium chloride, and then dry it at 85 °C for 12 hours. The remaining lithium chloride remains in the pore structure of the porous carbon to participate in the prelithiation of the subsequent charge and discharge process, obtaining the target product, the starch-based hard carbon anode material.
[0037] The specific surface area of this anode material was tested using a specific surface area tester, and the specific surface area was 142 m 2 / g.
[0038] Example 3 This example provides a preparation method of a starch-based hard carbon anode material, and the preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder into deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration polyvinyl alcohol transparent solution, and cool it to room temperature; then carefully mix 500 g of the polyvinyl alcohol solution with 100 g of a 10% mass concentration LiOH solution, add 400 g of wheat starch, stir at 45 °C for 5 h, and then add hydrofluoric acid with the same amount of substance as lithium hydroxide to react lithium hydroxide with hydrofluoric acid to generate lithium fluoride, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain small spherical precursors; S3: Using a tube furnace under an argon atmosphere, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of wheat starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, and it is heated from 400 °C to 950 °C, and maintained at 950 °C for 2.5 h to complete the carbonization process. The solid mixture after the reaction is ultrasonically cleaned in deionized water for 4 hours to wash away the excess lithium fluoride, and then dried at 85 °C for 12 hours. The remaining lithium fluoride remains in the pore structure of the porous carbon to participate in the prelithiation of the subsequent charge-discharge process, obtaining the target product, a starch-based hard carbon anode material.
[0039] The specific surface area of this anode material was tested using a specific surface area tester, and the specific surface area was 152 m 2 / g.
[0040] Example 4 This example provides a preparation method for a starch-based hard carbon anode material, and this preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder to deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration polyvinyl alcohol transparent solution, and cool to room temperature; then carefully mix 500 polyvinyl alcohol solutions with 100 g of a 10% mass concentration LiOH solution, add 400 g of potato starch, stir at 45 °C for 5 h, and then add hydrobromic acid with the same molar amount as lithium hydroxide to react lithium hydroxide with hydrobromic acid to generate lithium bromide, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain spherical precursors; S3: Using a tube furnace under an argon atmosphere, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of potato starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, and it is heated from 400 °C to 950 °C, and maintained at 950 °C for 2.5 h to complete the carbonization process. The solid mixture after the reaction is ultrasonically cleaned in deionized water for 4 hours to wash away the excess lithium bromide, and then dried at 85 °C for 12 hours. The remaining lithium bromide remains in the pore structure of the porous carbon to participate in the prelithiation of the subsequent charge-discharge process, obtaining the target product, a starch-based hard carbon anode material.
[0041] The specific surface area of this anode material was tested using a specific surface area tester, and the specific surface area was 157 m 2 / g.
[0042] Each comparative example in the present invention is used for comparison with Example 1.
[0043] Comparative Example 1 This comparative example provides a preparation method of a starch-based hard carbon negative electrode material, and the preparation method includes the following steps: S1: Add 450 g of corn starch to 100 g of a LiOH solution with a mass concentration of 10%, stir at 45 °C for 5 h, and then add dilute hydrochloric acid with the same amount of substance as lithium hydroxide to react lithium hydroxide with hydrochloric acid to generate lithium chloride, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain small spherical precursors; S3: Using a tube furnace under an argon atmosphere, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of corn starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, and it is heated from 400 °C to 900 °C, and kept at 900 °C for 3 h to complete the carbonization process. The solid mixture after the reaction is ultrasonically cleaned in deionized water for 4 hours to wash away the excess lithium chloride, and then dried at 85 °C for 12 hours. The remaining lithium chloride remains in the pore structure of the porous carbon to participate in the prelithiation of the subsequent charge and discharge process, obtaining the target product, the starch-based hard carbon negative electrode material.
[0044] The specific surface area of this negative electrode material was measured using a specific surface area tester, and the specific surface area was 101 m 2 / g.
[0045] Comparative Example 2 This comparative example provides a preparation method of a starch-based hard carbon negative electrode material, and the preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder to deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration of polyvinyl alcohol transparent solution, and cool to room temperature; then add 450 g of corn starch and stir at 45 °C for 5 h to obtain a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain small spherical precursors; S3: Under an argon atmosphere in a tubular furnace, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of corn starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, rising from 400 °C to 900 °C, and hold at 900 °C for 3 h to complete the carbonization process. Ultrasonically clean the solid mixture after the reaction in deionized water for 4 hours, and then dry it at 85 °C for 12 hours to obtain the target product, the starch-based hard carbon anode material.
[0046] The specific surface area of this anode material was tested using a specific surface area tester, and the specific surface area was 161 m 2 / g.
[0047] Comparative Example 3 This comparative example provides a method for preparing a starch-based hard carbon anode material, and this preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder to deionized water, stir at room temperature for 30 minutes to prevent caking, and then stir at 95 °C for 30 minutes to obtain a 10% mass concentration transparent polyvinyl alcohol solution, and cool it to room temperature; then add 450 g of corn starch to 500 g of the polyvinyl alcohol solution, stir at 45 °C for 5 h, then add 100 g of a 10% LiOH solution, mix carefully, and then add dilute hydrochloric acid with the same amount of substance as lithium hydroxide to react lithium hydroxide with hydrochloric acid to generate lithium chloride, obtaining a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain spherical precursors; S3: Under an argon atmosphere in a tubular furnace, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min; between 200 °C and 400 °C, this process is the tar removal stage of corn starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure; subsequently, the heating rate is 5 °C / min, rising from 400 °C to 900 °C, and hold at 900 °C for 3 h to complete the carbonization process. Ultrasonically clean the solid mixture after the reaction in deionized water for 4 hours to wash away the excess lithium chloride, and then dry it at 85 °C for 12 hours. The remaining lithium chloride remains in the pore structure of the porous carbon to participate in the prelithiation effect of the subsequent charge and discharge process, obtaining the target product, the starch-based hard carbon anode material.
[0048] The specific surface area of this anode material was tested using a specific surface area tester, and the specific surface area was 126 m 2 / g Comparative Example 4 This comparative example provides a method for preparing a starch-based hard carbon anode material, and this preparation method includes the following steps: S1: Add polyvinyl alcohol (PVA) powder into deionized water, stir for 30 minutes at room temperature to prevent caking, and then stir for 30 minutes at 95 °C to obtain a 10% mass concentration transparent polyvinyl alcohol solution. Cool it to room temperature. Then carefully mix 500 g of the polyvinyl alcohol solution with 178 g of a 10% lithium chloride solution, and add 450 g of corn starch. Stir at 45 °C for 5 h to obtain a reaction mixture; S2: Dropwise inject the prepared reaction mixture into a liquid nitrogen bath to quickly freeze the solution to obtain spherical precursors; S3: Under an argon atmosphere in a tube furnace, heat the precursor from room temperature to 200 °C at a heating rate of 5 °C / min. Between 200 °C and 400 °C, this process is the stage of tar removal from corn starch, and a very slow heating rate of 1 °C / min is required to avoid the collapse of the pore structure. Subsequently, increase the heating rate to 5 °C / min and heat from 400 °C to 900 °C, and hold at 900 °C for 3 h to complete the carbonization process. Ultrasonically clean the reacted solid mixture in deionized water for 4 hours to wash away the excess lithium chloride, and then dry at 85 °C for 12 hours. The residual lithium chloride remains in the pore structure of the porous carbon to participate in the prelithiation of the subsequent charge-discharge process, obtaining the target product, a starch-based hard carbon anode material.
[0049] Test the anode material with a specific surface area tester. The specific surface area is 153 m 2 / g.
[0050] Prepare button cells from the anode materials prepared in the above examples and comparative examples according to the button cell process and conduct tests. The test results are shown in Table 1.
[0051] The preparation process of the button cell is as follows: Respectively use the anode materials prepared in the above examples and comparative examples as anode active substances, mix them evenly with polyvinylidene fluoride (PVDF) (dissolved in N-methylpyrrolidone) and conductive carbon black in a mass ratio of 90:5:5, coat them into an electrode film, place them in a vacuum drying oven and dry at 120 °C for 12 h, roll and punch to obtain anode sheets; use a PP film as the button cell separator and a lithium metal sheet as the counter electrode. Assemble the above obtained hard carbon anode sheets into 2430 button cells in a glove box and test their electrochemical performance (test voltage (0 - 3) V, current 0.05C). The results are shown in Table 1; Table 1 It can be seen from the data in the above table that the anode materials prepared in the examples of the present invention all have excellent electrochemical performance.
[0052] Comparative Example 1 is the material prepared without a template. Although the initial efficiency is not affected, the specific capacity decreases significantly. In Comparative Example 2, although there is a template, the prelithiation salt is lacking. The specific capacity is relatively high, but the initial efficiency drops significantly. In Comparative Example 3, the polyvinyl alcohol solution is first mixed with starch, and then lithium hydroxide and hydrochloric acid are added successively. Since starch will block the pores of the polyvinyl alcohol template, resulting in less prelithiated salt entering the pores, both the initial efficiency and the specific capacity are affected. In Comparative Example 4, lithium chloride solution is directly added. Because the hydroxide group of lithium hydroxide in Example 1 has the property of similar solubility with the hydroxyl group of polyvinyl alcohol, lithium hydroxide can enter the template pores better. If lithium chloride salt is directly added, the absence of hydroxide group will lead to less prelithiated salt in the pores, affecting the initial efficiency.
[0053] Inspired by the ideal embodiments of the present invention described above, through the above description, relevant staff can make various changes and modifications completely within the scope without departing from the technical idea of this invention. The technical scope of this invention is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a starch-based hard carbon negative electrode material, characterized in that: The steps include: S1: mixing a polyvinyl alcohol solution and a lithium hydroxide solution, adding starch, stirring, and then adding a halogenated acid to react to obtain a reaction mixture; S2: injecting the reaction mixture dropwise into a liquid nitrogen bath to obtain a spherical precursor; S3: Under an inert gas atmosphere, the spherical precursor is calcined to obtain a starch-based hard carbon negative electrode material.
2. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the starch to the polyvinyl alcohol is (8-10):
1.
3. The method for preparing a starch-based hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of lithium hydroxide to polyvinyl alcohol is 1:
5.
4. The method for preparing a starch-based hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The starch is selected from at least one of cereal starch, potato starch and bean starch.
5. The method for preparing a starch-based hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: Step S3 includes: in an inert gas atmosphere, heating the spherical precursor from room temperature to 200° C., from 200° C. to 400° C., and then from 400° C. to 900-1000° C. for calcination to obtain a starch-based hard carbon negative electrode material.
6. The method for preparing a starch-based hard carbon negative electrode material according to claim 5, characterized in that: When the spherical precursor is heated from room temperature to 200° C., the heating rate is 5° C. / min.
7. The method for preparing a starch-based hard carbon negative electrode material according to claim 5, characterized in that: When the spherical precursor is heated from 200° C. to 400° C., the heating rate is 1° C. / min.
8. The method for preparing a starch-based hard carbon negative electrode material according to claim 5, characterized in that: When the spherical precursor is heated from 400° C. to 900-1000° C., the heating rate is 5° C. / min.
9. A starch-based hard carbon negative electrode material, characterized in that: The method is used to prepare the starch-based hard carbon negative electrode material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the starch-based hard carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Fast-charging hard carbon negative electrode material as well as preparation method and application thereof
CN114430038A
Hard carbon negative electrode material and preparation method and application thereof
CN114497545A
Carbon negative electrode material and preparation method thereof, lithium ion battery negative electrode, lithium ion battery and electric equipment
CN115377414A
Starch-based hard carbon sodium ion battery negative electrode material as well as preparation method and application thereof
CN116544386A
Hard carbon negative electrode material and preparation method therefor, mixed negative electrode material, and secondary battery
WO2024108771A1
Cited By
Boron-containing compound modified lithium ion battery hard carbon negative electrode material as well as preparation method and application thereof
CN121672494A